Transformasi Akad Mudharabah di Era Digital : Inovasi Fintech Syariah dalam Meningkatkan Transparansi dan Akurasi Investasi - Kesy Yumaida Kasih; Fiska Ummyza; Rini Putri; Rani Safitri; Rini Elvira (Universitas Veteran Bangun Nusantara, 2025)
This study discusses the application of sharia fintech with mudharabah contracts in the perspective of sharia microeconomics, particularly in relation to the principles of ownership, principal-agent relationships, pricing, sharia investment, and digital financing governance. The main issue examined is the emergence of challenges in the distribution and monitoring of profits in digital mudharabah financing, such as asymmetric information, moral hazard, and adverse selection, which have the potential to disrupt the principles of justice and trust. This study aims to analyze relevant Islamic microeconomic concepts and theories, examine the causes and effects of challenges in digital mudharabah financing, and formulate the best Islamic governance to be in line with the principles of justice, trustworthiness, and maslahah. The method used is a literature study with a qualitative-descriptive approach to scientific journals, books, and Sharia sources such as the Qur'an, hadith, fiqh rules, and maqasid Sharia. The results of the study show that sharia fintech has great potential in increasing financial inclusion and transparency in mudharabah financing, but its effectiveness is still limited by weak monitoring systems, limited digital infrastructure, and low information disclosure. The synthesis of findings shows that strengthening governance through real-time reporting transparency, smart contract implementation, strict screening, and integrated digital monitoring are the main solutions. This study concludes that strong, technology-based sharia governance is the key to the success of digital mudharabah that is fair, trustworthy, and oriented towards public benefit.